1961
DOI: 10.1083/jcb.9.1.81
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Penetration of Mammalian Cells by Deoxyribonucleic Acids

Abstract: Tritium-labeled deoxyribonucleic acid (DNA) from pneumococci and from human leukocytes was added to growing cultures of HeLa cells at 37°C. Autoradiography revealed an extensive localization of tritium in the nuclear regions. The label could not be removed by treatment with ribonuclease or dilute perchloric acid, but quantitative removal from the cells could be effected with deoxyribonuclease. Chemical and radioactivity determinations on nucleic acids isolated from the exposed HeLa cells revealed the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 27 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…If this difference is real, it could represent reutilization of labeled FL cell DNA, or FL cell D N A breakdown product. The phenomenon of D N A reutilization has been suggested in a n u m b e r of other systems (4-7, 9, 10, 16, 23), in which tritium-labeled DNA, available as purified D N A (4,16,23) or available in nuclei of infused leukocytes (5,7) or in degenerating liver cells or lymphocytes (6,23), appeared in the nuclei of rapidly dividing transplanted tumor cells, or in dividing cells of the gut, testis, etc. An obvious parallel to these observations exists in our own experiments in which degenerating FL cells are typically present in the center of FL colonies (2), and could serve as a source of diffusible label to multiplying fibroblasts.…”
Section: Bone Induction By Labeled Fl Cellsmentioning
confidence: 95%
“…If this difference is real, it could represent reutilization of labeled FL cell DNA, or FL cell D N A breakdown product. The phenomenon of D N A reutilization has been suggested in a n u m b e r of other systems (4-7, 9, 10, 16, 23), in which tritium-labeled DNA, available as purified D N A (4,16,23) or available in nuclei of infused leukocytes (5,7) or in degenerating liver cells or lymphocytes (6,23), appeared in the nuclei of rapidly dividing transplanted tumor cells, or in dividing cells of the gut, testis, etc. An obvious parallel to these observations exists in our own experiments in which degenerating FL cells are typically present in the center of FL colonies (2), and could serve as a source of diffusible label to multiplying fibroblasts.…”
Section: Bone Induction By Labeled Fl Cellsmentioning
confidence: 95%
“…Penetratiorvof mammalian cells by DNA has been observed in a number of laboratories. [13][14][15][16][17][18] Reports have also appeared concerning the physiological effects of exogenous DNA. Three different groups have observed genetic transformation of mammalian cells by mammalian DNA in tissue culture.5,19,20 However, the cells transformed represented only a tiny fraction of the total number exposed to the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The indication that intact DNA was incorporated in some experiments gained support from the studies of Borenfreund and Bendich (19) who employed an antibody against DNase to demonstrate the incorporation of polymerized DNA by HeLa cells in vitro. Kay (20) has reported that once DNA is incorporated it may be utilized without intracellular degradation.…”
Section: Conditions and Significance Of Reutilization Of Dna And Its mentioning
confidence: 91%